Malaria Dynamics at LCHCS Bilwi, Nicaragua 2013-2020. (Revista Torreón Universitario, 2022)
Malaria continues to be a public health problem, the WHO estimates, in its 2020 report, that 229 million cases occurred worldwide. Nicaragua in 2011, reported a national reduction of 75% of malaria cases, but in that same year the MINSA, through the Malaria component, establishes a scenario where the trend of reduction deteriorates and places it in the RACCN, specifically, in the SILIAS Bilwi. The objective of this study is to show the dynamics of malaria in the SILAIS Bilwi during a period of eight years (2013 to 2020). Through a retrospective descriptive study, the results show that Bilwi reported an increase in autochthonous cases caused mainly by Plasmodium vivax, concentrating these cases, in the urban area of Puerto Cabezas, reporting an increase of 22% (2,403) during the study period 2013-2015, compared to 2012, from 2016 to 2018 it was 71.77% (27,102) and  2019 to 2020 was 69% (35,930), the age groups most affected were young people and people of active working age, sex was not a risk factor, the values obtained did not show significant differences, ethnicity was more Miskitu was affected with 91.43%, in the area it is the one with the greatest presence, but this area is rich in ethnic culture, a condition that represents a challenge for the health authorities to address the disease.
Keywords: ethnics groups; Malaria; LCHCS Bilwi